Regulation of Nitrate Assimilation in Maize and Barley - Zoumadakis, Michael (My University, 1989)
To determine the limiting factors in nitrate assimilation in maize and barley, the effects of nitrate on 1) steady state levels of nitrate reductase activity (NRA) and nitrate reductase protein (NRP); 2) the uptake, translocation and accumulation of nitrate in the shoots of the seedling plant were examined. Seedlings were grown on Kimpack paper containing l, 5 or 20mM KN0₃ for 7 days at 20°c (barley) or 28°C (maize). At lmM KN0₃ the rate of 3 nitrate uptake and the levels of NRA and NRP were higher in maize than in barley. In contrast., at 5 and 20mlv1 KNo₃, the rate of uptake, the accumulation of nitrate and the NRA were higher in barley than in maize. The results suggest that the synthesis of NR is induced by lower levels of nitrate in maize relative to barley. In addition, nitrate-nitrogen appears to be more efficiently converted to proteins, other than NR, in maize than in barley. At very low levels of nitrate an inactive NR protein was present. in maize. To characterize the inactive NR, maize plants were grown under conditions where high levels of NRA were detected (vermiculite:sand, l:lw/w, containing 10mM KN0₃) and under conditions where NR was present primarily in the inactive form (Kimpack paper:washed sand). Nitrate reductase was purified from primary leaves using Blue Sepharose affinity chromatography. The column was washed with NADH and KN0₃ in each case. The peaks of NR were 3 detected using Dot-immunoblotting, with an antibody prepared against maize leaf NR and by assessing the NRA. Active and inactive NR forms were found both at the NADH-and the KN0₃-wash. In the NADH-wash, the inactive NR as compared to the active form, has very low NADH (complete), FMNH₂, MV and BPB (reductase) activities. Significant levels of cyt-c and FeCN (dehydrogenase) partial activities were detected. Similarly, the inactive NR in the KN0-wash, had 3no NADH (complete), FMNH2 , MV and BPB (reductase) activities. Very low levels of cyt-c and FeCN (dehydrogenase) NR partial activities were detected, compared to the respective activities of the active enzyme in the KNO₃ wash.
Regulation of Nitrate Assimilation
Keywords: maize; barley; nitrate assimilation